Traditional use of Polypores in Georgia (the Caucasus) - Jorjadze, Angelina; Bussmann, Rainer W; Paniagua Zambrana, Narel Y; Batsatsashvili, Ketevan; Svanidze, Eter (Ethnobotany Research and Applications, 2023)
Background: This paper describes traditional uses of polypore fungi in Georgia (the South Caucasus). Methods: We used ethnomycological interviews collected in 2014–2017 in various regions of the country and available literature data. Results: The research revealed eight polypore species traditionally used Georgia: Cerioporus squamosus, Daedalea quercina, Fistulina hepatica, Fomes fomentarius, Fomitopsis betulina, Laetiporus sulphureus, Panus rudis, Sparassis crispa. Conclusions: Knowledge on medicinal uses of the species is lost in the population at present and can only be found in ethnographic/linguistic literature. The paper presents vernacular names of the polypore species with their Latin identifications and various uses (for food, medicine, decorations and tinder) with respective sources cited. Keywords: Ethnomycology, Polypores, Traditional knowledge, Georgia, the Caucasus